2022
DOI: 10.1007/s00264-021-05278-w
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic characteristics of broaching procedure for post-operative stem subsidence in cementless total hip arthroplasty

Abstract: Purpose: Avoiding stem subsidence is crucial for achieving better outcome for cementless Total hip arthroplasty (THA). The aim of this study was to develop a prediction model for the incidence of post-operative stem subsidence using fullquantitative acoustic parameters in hammering sound during the broaching procedure and to assess the accuracy of this prediction model. Methods:The acoustic parameters of the hammering sounds during a broaching procedure for 55 hips in 49 patients underwent THAs with cementless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The frequency components that constitute the hammering sound are the characteristic frequencies of the hammer and the inserter [11]. Zhuang et al stated that the frequency components of the hammering sound are almost independent of the manufacturers of the inserter and hammer [1]. Based on previous research, we reported that the peak frequency is approximately 3 kHz [10].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The frequency components that constitute the hammering sound are the characteristic frequencies of the hammer and the inserter [11]. Zhuang et al stated that the frequency components of the hammering sound are almost independent of the manufacturers of the inserter and hammer [1]. Based on previous research, we reported that the peak frequency is approximately 3 kHz [10].…”
Section: Discussionmentioning
confidence: 65%
“…Total hip arthroplasty (THA) is a surgical procedure to replace a hip joint, with hip prostheses, that Open Access has lost its functionality. The developments in hip arthroplasty over recent years have aimed to improve outcomes, reduce complications [1][2][3]. However, it has been reported that during surgery, serious intraoperative fractures occur at a rate between 0.4% and 4.9% [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Goossens et al reported that frequency below 2 kHz was crucial to reflect the process of implant insertion [15]. And our previous study demonstrated a successful result that used both low and high range frequency acoustic parameters to predict postoperative stem subsidence [16].…”
Section: Introductionmentioning
confidence: 69%
“…We believe that quantitative evaluation of the hammering sounds should be the future gold standard in cementless THA, as auditory sensations are subjective and differ among individuals; in contrast, acoustic analysis is objective and far more precise and accurate. Many recent studies have demonstrated the potential usefulness of acoustic assistance in THA [ 10 , [12] , [13] , [14] , [15] ]. Better clinical outcomes of cementless THA have resulted from improvements in the cementless stem itself as well as technologies such as preoperative three-dimensional templating [ 16 , 17 ], navigation systems [ 18 , 19 ], and robotics [ [20] , [21] , [22] ].…”
Section: Discussionmentioning
confidence: 99%